Endocan is a predictor of increased cardiovascular risk in women with polycystic ovary syndrome. (3rd April 2017) - Bicer, Merve; Guler, Aslı; Unal Kocabas, Gokcen; Imamoglu, Cetin; Baloglu, Ali; Bilgir, Oktay; Yuksel, Arif; Bozkaya, Giray; Calan, Mehmet
ABSTRACT: Purpose : Endocan is a proteoglycan secreted mainly from endothelial cells. It has been implicated that there is a link between endocan and endothelial dysfunction. Polycystic ovary syndrome (PCOS) is a reproductive and metabolic disease associated with increased risk of cardiovascular events. The aims of this study were to ascertain whether circulating endocan levels are altered in women with PCOS, and whether there is an association between endocan and carotid intima media thickness (cIMT).Materials and methods : This cross-sectional study included 80 women with PCOS and 80 age- and BMI-matched controls without PCOS. Circulating endocan levels were measured using ELISA. Metabolic, hormonal parameters and cIMT were determined. 2-h oral glucose tolerance test (2-h OGTT) was performed on all women.Results : Circulating endocan levels were significantly elevated in women with PCOS compared with controls (5.99 ± 2.37 vs. 3.66 ± 1.79 ng/ml, P < 0.001). Endocan levels positively correlated with BMI, homeostasis model assessment of insulin resistance (HOMA-IR), free androgen index (FAI), high-sensitivity C-reactive protein (hs-CRP), and cIMT in both PCOS and control groups. Endocan levels did not correlate with fasting blood glucose, 2-h OGTT, A1C and lipid parameters. Multiple linear regression analysis revealed that endocan is an independent predictor for cIMT ( β = 0.128, 95% CI = 0.118–0.138, P = 0.011).Conclusions : Circulating endocan levels are significantly higher in women with PCOS and endocan is independently associated with cIMT. Elevated endocan levels can be a predictor of increased cardiovascular risk in PCOS subjects.